Potresna analiza armiranobetonskih stavb s poenostavljenimi nelinearnimi modeli - Jamšek, Aleš (Gradbeni vestnik, 2019)
In the first part of the paper, we present the improved fish-bone (IFB) model for the seismic analysis of predominantly plan-symmetrical reinforced concrete frame buildings and develop a simplified nonlinear model for the analysis of a simple reinforced concrete (RC) wall-frame building, consisting of the IFB model and a model of a cantilever wall. The configuration of structural elements of the IFB model is equal to that of the basic fish-bone model, which is determined by a column to which beams are connected at both sides and in all storeys. The improvement of the basic fish-bone model refers to a new procedure for the estimation of the parameters of the structural elements, which allows to approximately account for the effect of the structural elements on the seismic response of a building. In the second part of the paper, we analyse the ability of simplified nonlinear models for seismic analysis. First, we show that the IFB model is sufficiently accurate to simulate the storey-based engineering demand parameters of a four-storey reinforced-concrete frame building, since the obtained results do not differ significantly from the results of the pseudo-dynamic test and the results of the seismic analysis performed with the conventional nonlinear model of RC building. Then follows the analysis of the capability of the simplified nonlinear models for pushover analysis of symmetric RC buildings, where we considered a four-storey RC frame building, an eight-storey frame building and an eight-storey wall-frame building. We found that the simplified models used in the analysis are sufficiently accurate for the calculation of the pushover curves and the storey-based damage assessment of structural elements. The use of the presented simplified nonlinear models is currently limited to the seismic analysis of plan-symmetrical buildings subjected to seismic excitation in one horizontal direction only.
Keywords: armiranobetonska stavba; fish-bone model; MDOF model; model MDOF; model ribje kosti; poenostavljen nelinearni model; potisna analiza; pseudo-dynamic test; psevdo-dinamični test; pushover analysis; reinforced concrete building; simplified nonlinear model